Pengembangan E-Modul Berbasis Projek Penguatan Profil Pelajar Pancasila (P5) sebagai Sumber Belajar Berdiferensiasi untuk Matematika SMP - Tyaningsih, Ratna Yulis; Baidowi; Azmi, Syahrul; Lu'luilmaknun, Ulfa (FKIP Universitas Mataram, 2024)
The Pancasila Student Profile Strengthening Project (P5) is a form of implementation of the independent curriculum that aims to provide students with a more meaningful learning experience and process. P5 activities also apply the concept of differentiated learning, which emphasizes adapting to students' learning interests and readiness to obtain good learning results. Data in the field shows the lack of availability of the P5 module developed at SMPN 1 Pujut which is used as a guide for teachers and students in carrying out P5 activities. This research aims to create an E-Module based on the Strengthening Pancasila Student Profile (P5) Project as a Differentiated Learning Resource for Middle School Mathematics that is suitable for use. This type of research is Research and Development (R&D) using Plomp design research, including (1) preliminary research, (2) development or prototyping phase, and (3) assessment phase. The results of this research indicate that the P5 e-module is classified in the very valid category with content validity criteria of 90.28%, and construct validity of 90.97%. Therefore, the availability of interactive P5 modules helps teachers provide innovative ideas and references for creating similar or even better modules.